A Critical Discourse Analysis of “Discrimination Starts Before and Lasts Our Entire Lives” Speech by Charlotte Helene Fien: Discrimination Through Termination - Ayuningtyas, Inggita Pramesti; Kusumawardani, Maria Regina Anna Hadi (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
Down syndrome people are often underestimated by society. It is because of their disability to do difficult things and their physical appearances. This common opinion has been broken by Charlotte Helene Fien, a representative of Down Syndrome people at the United Nations. This issue results in a social wrong which is covered by the society’s justification. This social wrong is indirectly depicted in Charlotte’s speech. The aim of this research is to uncover the social wrong that evolves in our society. The method used in this research is four stages by Roy Bhaskar (1986). SFG is utilized in this research to give linguistic evidence in interpreting the speech. The results show that social wrong found in the speech is termination of Down Syndrome babies. It is hard to be found because society is a lack of awareness about life values and it is considered as normal and true. However, this social wrong is still needed in the society because it gives benefits for parents and improves society’s standard of living. In order to stop this social wrong, society has to change their opinion, take real actions, and make policies to protect people with Down Syndrome.